A Newly Discovered Humic-Reducing Bacterium, Pseudomonas geniculata PQ01, Isolated From Paddy Soil Promotes Paraquat Anaerobic Transformation - Wu, Chunyuan; Wu, Xiaoyan; Chen, Shanshan; Wu, Dongming (Frontiers in Microbiology, 2020)
Due to toxicity and persistence of paraquat (a widely used herbicide), eco-friendly remediation approaches to its contamination and effective antidotes to its poisoning have been highly desired and raised increasing concerns. Paraquat degradation was lesser in aerobic soil in comparison with anaerobic soil, and humic-reducing microorganisms (HRMs) play a key role in paraquat anaerobic transformation process. However, the degradation pathways and related mechanisms remain poorly understood. In this study, we investigated the specific interaction mechanisms of the paraquat transformation processes mediated by a humic-reducing strain under anaerobic conditions. A strain of pure culture, designated as PQ01, was successfully isolated from paddy soil using anaerobic enrichment procedure, and identified as Pseudomonas geniculata using phenotypic and phylogenetic analysis. Sucrose, glucose, pyruvate, formic acid, and acetic acid were shown to be favorable electron donors for the reduction of anthrahydroquinone-2,6-disulfonate (AQDS) reduction by PQ01. The strain also had the ability of reducing Fe(III) (hydr)oxides in the presence of sucrose with efficiencies in the order of ferrihydrite > α-FeOOH/γ-FeOOH > γ-Fe2O3 > α-Fe2O3. In the “PQ01 + paraquat + AQDS + sucrose” system, AQDS reduction and paraquat biotransformation by strain PQ01 occurred simultaneously, and the presence of sucrose significantly enhanced the biotransformation. Specific mechanisms of the electron transfer processes are promoted by both PQ01 and AQDS, and proceed in two aspects: (1) paraquat served as electron donor in the anaerobic reduction of AQDS by strain PQ01; (2) AQDS was reduced by PQ01 anaerobic metabolism to produce AH2QDS, which can directly react with paraquat under anaerobic conditions to generate a single crystal compound (molecular formula of the unit structure is C26H20N2O8S2), causing the paraquat to decline dramatically. In conclusion, this main mechanism included the microbial reduction of AQDS to AH2QDS, followed by the abiotic reaction between AH2QDS and paraquat. This study reported the new characteristics of P. geniculata capable of reducing humics analogs, Fe(III) (hydr)oxides, and paraquat, and proposed a novel electron transformation mechanism of the HRMs’ mediated degradation of organic contaminants.